Darling doll - Troupe, Thomas Kingsley; Faber, Rudy (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2017)
Even after three episodes of ghost-hunting, sixth-grader Casey thought that asking Beth Markle to dance at the Spring Fever Dance was the scariest thing he had ever done--but that was before he encountered the creepy doll made by the long-defunct Darling Doll Company, which is currently possessed by the ghost of the company's owner
English stories
RL: 4-6
1 2 13 15
NEW_ZTN_GN
Keywords: Antiques business -- Juvenile fiction; Dolls -- Juvenile fiction; Friendship -- Juvenile fiction; Paranormal fiction; Sisters -- Juvenile fiction; Twins -- Juvenile fiction; Antiques -- Fiction; Dolls -- Fiction; Friendship -- Fiction; Mystery and detective stories; Sisters -- Fiction; Spirit possession -- Fiction; Supernatural -- Fiction; Twins -- Fiction; Detective and mystery fiction; Mystery fiction